Budaya Kewarganegaraan (Civic Culture) Melalui Kegiatan Ekstrakurikuler Pramuka di SMK Sore Tulungagung - Catur Kukuh Santoso; Ahmad Izzul Ito; Nurna Listya Purnamasari (Lembaga Pengembangan Kinerja Dosen, 2024)
Civic culture is the attitude and behavior of every member of society or a group that is socially recognized and considered important by the school, community and state and shows politeness, responsibility, care, openness and love for the nation. The aim of this research is (1) to describe the implementation of scout extracurricular activities at Vocational High School Sore Tulungagung, and (2) to find out what elements of civic culture are found in scout extracurricular activities at Vocational High School Sore Tulungagung. This research uses qualitative research with a qualitative descriptive approach. Data sources were obtained from interviews, observations and documentation studies. The results of the research show that: (1) The implementation of scout extracurricular activities at Vocational High School Sore Tulungagung has been carried out well and in line with expectations.. This is proven by the implementation of 5 Scout activities including: regular scout training, long march bhakti ambalan, perkasa, mustegak, joint scout training and (2) Elements of civic culture found in scout extracurricular activities at Vocational High School Sore Tulungagung including: active participation, solidarity, tolerance, social networking, and mutual cooperation. Where these elements are different but still continuous.